Keabsahan Penggunaan Kartu Tanda Penduduk (KTP) sebagai Objek Jaminan Hutang - Alvieony Dhaniva Putri; Aris Yuni Pawestri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The use of Identity Cards (Kartu Tanda Penduduk/KTP) as collateral in debt agreements remains common despite the absence of legal provisions recognizing KTP as a valid security object. This study analyzes the legal validity of using KTP as collateral and the legal consequences arising when a debtor defaults. A normative juridical method was employed using statutory and conceptual approaches, with primary, secondary, and tertiary legal materials analyzed through qualitative legal interpretation. The results show that KTP cannot be classified as either proprietary or personal security because it is an official state identity document with no economic value and does not fulfill the legal requirements of collateral under Indonesian civil law. Consequently, KTP cannot establish preferential rights for creditors or function as an executable security object in the event of default. Moreover, retaining a debtor’s KTP as collateral may violate the principles of personal data protection under Indonesian law. Although the principal debt agreement may remain valid if it fulfills Article 1320 of the Indonesian Civil Code, the collateral agreement involving KTP is legally invalid. Strengthening public legal awareness and government supervision is recommended to prevent misuse of identity documents in private debt transactions.